2017
DOI: 10.1002/ejlt.201600390
|View full text |Cite
|
Sign up to set email alerts
|

Rump and shoulder muscles from grass and linseed fed cattle as important sources of n‐3 fatty acids for beef consumers

Abstract: Ground beef has potential to be a relatively inexpensive and sustainable source of n‐3 fatty acids (FA) for people who frequently consume it, but don't consume n‐3 containing fish. To enhance n‐3 FA content in ground beef, we evaluated FA content in pertinent muscles from grass‐fed cattle that were supplemented with flaxseed for 75 days before slaughter and compared them with loin muscle from these cattle. Lipids from rump (m. biceps femoris), shoulder (m. triceps brachii), and loin (m. longissimus dorsi) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…However, other authors reported no decrease in EPA and DHA during cooking [70,83,112,113,114,115,116,117,118,119,120,121,122,123]. Indeed, products such as raw fish and production animals do not contain EPA and DHA in pure chemical form, but as components of phospholipids integrated into cell membranes, which have comparatively low susceptibility to degradation [82,124].…”
Section: Assumption 5: Culinary Treatments Decrease Epa and Dha Inmentioning
confidence: 99%
“…However, other authors reported no decrease in EPA and DHA during cooking [70,83,112,113,114,115,116,117,118,119,120,121,122,123]. Indeed, products such as raw fish and production animals do not contain EPA and DHA in pure chemical form, but as components of phospholipids integrated into cell membranes, which have comparatively low susceptibility to degradation [82,124].…”
Section: Assumption 5: Culinary Treatments Decrease Epa and Dha Inmentioning
confidence: 99%
“…Whilst it is well established that seafood, including fish species, provide the highest levels of long-chain omega-3 fatty acids, its overall consumption is low (Byelashov, Sinclair & Kaur, 2015). Consequently, red-meat derived omega-3 is estimated to make a significant contribution towards the daily requirements of these fatty acids (Howe, Buckley & Meyer, 2007;Kronberg, Scholljegerdes, Maddock, Barceló-Coblijn & Murphy, 2017;Purchas, Wilkinson, Carruthers & Jackson, 2014).…”
mentioning
confidence: 99%